2015
DOI: 10.3906/sag-1406-76
|View full text |Cite
|
Sign up to set email alerts
|

Malnutrition is associated with dementia severity and geriatricsyndromes in patients with Alzheimer disease

Abstract: Background/aim: Malnutrition is associated with increased morbidity and mortality in patients with Alzheimer disease (AD). In this study, we aimed to screen for malnutrition and geriatric syndromes and seek their associations in patients with AD. Materials and methods:The Mini Mental State Examination (MMSE), Mini Nutritional Assessment (MNA), Katz Activities of Daily Living (ADL), and Lawton Instrumental Activities of Daily Living (IADL) tests were applied. Mean daily oral fluid intake was assessed according … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 14 publications
1
25
0
5
Order By: Relevance
“…Several possible mechanisms have been suggested to explain the effect of serum albumin on MCI risk. First, serum albumin is associated with nutritional status in elderly (Covinsky et al 2002), and persistent malnutrition plays an important role in cognitive impairment (Yildiz et al 2015;Karakis et al 2016). Therefore, relatively low serum level of albumin partly reflects the malnutrition, which promotes the progression of MCI.…”
Section: Discussionmentioning
confidence: 99%
“…Several possible mechanisms have been suggested to explain the effect of serum albumin on MCI risk. First, serum albumin is associated with nutritional status in elderly (Covinsky et al 2002), and persistent malnutrition plays an important role in cognitive impairment (Yildiz et al 2015;Karakis et al 2016). Therefore, relatively low serum level of albumin partly reflects the malnutrition, which promotes the progression of MCI.…”
Section: Discussionmentioning
confidence: 99%
“…Dietary patterns of older adults usually contain low amounts of macro and micronutrients (calcium, iodine, vitamin B2, zinc, phosphorus, and vitamin B12) [Rakıcıoğlu et al, 2015] and it is high in carbohydrates [Boirie et al, 2014]. Dietary imbalances in older adults may determine several systemic conditions, including, frailty [Boulos et al, 2016], sarcopenia [Relph, 2016], dependency [Yildiz et al, 2015], dementia [Naseer et al, 2016], sleep disorders [Yildiz et al, 2015], increased risk of falls [Masumoto et al, 2015], mortality [Tsai et al, 2016] and higher rates of hospitalization [Geurden et al, 2015]. As a way to counteract this problem, a range of dietary supplements including milk-based drinks fortified with different nutrients are commercially available.…”
Section: Introductionmentioning
confidence: 99%
“…Cova et al (2016) reported that progression towards AD and dementia is expected when weight loss is observed in mild cognitive impairment. Malnutrition is associated with dementia severity and geriatric syndrome in AD patients (Yildiz et al, 2015). Various explanations have been proposed for weight loss such as atrophy of mesial temporal cortex, biological disturbance or feeding behavior.…”
Section: Discussionmentioning
confidence: 99%